2014
DOI: 10.1519/jsc.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Does Performing Drop Jumps With Additional Eccentric Loading Improve Jump Performance?

Abstract: Previous investigators have speculated that applying additional external load throughout the eccentric phase of the jumping movement could amplify the stretch-shortening cycle mechanism and modulate jumping performance and jump exercise intensity. The aims of this study, therefore, were to determine the effect of increased eccentric phase loading, as delivered using an elastic device, on drop jumps (DJs) performed from different drop heights. Of specific interest were changes in (a) the kinetics; eccentric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 24 publications
5
56
2
Order By: Relevance
“…Several eccentric‐phase variables (eg, peak velocity, peak force, RFD) have been shown to be sensitive to change in response to various strength training methodologies. In the present study, increases in eccentric‐phase kinetic energy were observed in both unknown (UL) and known load (KL) training groups (ES=0.98‐1.38 and 0.75‐1.09, for UL and KL, respectively) along with significant increases in eccentric velocity (ES=1.10‐1.33 and 0.39‐0.98).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Several eccentric‐phase variables (eg, peak velocity, peak force, RFD) have been shown to be sensitive to change in response to various strength training methodologies. In the present study, increases in eccentric‐phase kinetic energy were observed in both unknown (UL) and known load (KL) training groups (ES=0.98‐1.38 and 0.75‐1.09, for UL and KL, respectively) along with significant increases in eccentric velocity (ES=1.10‐1.33 and 0.39‐0.98).…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, changes in the pattern of neural activation in the early muscle activation period during the SSC could potentially influence the force at the start of the concentric phase. Indeed, Aboodarda et al . observed earlier quadriceps, biceps femoris and soleus EMG activity onsets when participants performed a drop jump with an additional load of 30% body mass.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, by increasing the loading during the eccentric phase it can further increase vertical jump height, such as in the depth jump [6]. Numerous studies have also compared the efficacy of a loaded eccentric phase using an additional 20-30% of body mass on a drop jump, which also led to an increase in subsequent jump height in (highly) trained athletes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the higher absolute loading required of AEL makes it an attractive strategy for applying additional stress to the muscle and connective tissue while maintaining the CON stimulus. The ability to preserve mechanical similarity and coupled actions may also explain previous reports of favorable changes in jumping and throwing actions, demonstrating that the training effects from AEL may transfer well to sport tasks and performance when applied to both strength and PT exercises [117][118][119][120][121][122][123][124]. Maintaining technical quality has important practical implications as well as including a reduced risk of injury in its application.…”
Section: Accentuated Eccentric Loadingmentioning
confidence: 84%